PP-002 Extemporaneous preparation of oral liquid formulation of acitretin. (25th February 2017) - Antolović-Amidzić, A; Stiblik-Stipešević, S; Bogdan, M
Abstract : This abstract was published in error and withdrawn at the author's request.